Barriers to adopting inherently safer design philosophy in Iran. Issue 2 (14th September 2017) - Jafari, Mohammad Javad; Nourai, Farshad; Pouyakian, Mostafa; Torabi, Seyed Ali; Rafiee Miandashti, Masoud; Mohammadi, Heidar
Abstract : Inherently safer design (ISD) is the best option to design of safer, cheaper, healthier, and more economic process plants, although this situation of its implementation in the real cases is not satisfying as it should be. This study aimed at explore the barriers influencing adopting ISD philosophy in Iran as a developing country with high potential development in process industries. In this qualitative study, a total of 47 experts—process designers and process safety engineers working in the oil, gas, petrochemical, and chemical manufacturing industries of Iran—participated, and data were gathered through a semiconstructed interview. Data analysis was conducted using the deductive content analysis method. Five categories and 21 subcategories were identified as barriers to the adoption of ISD in Iran, including organization‐related barriers (eight factors), inherent‐safety‐related barriers (three factors), legal‐ and regulation‐related barriers (four factors), technology‐related barriers (three factors), and academic‐related barriers (three factors). This study revealed that there are several barriers to the adoption of ISD philosophy in Iran, and negligence to address these barriers can negatively affect such adoption. © 2017 American Institute of Chemical Engineers Process Saf Prog 37: 221–229, 2018